How Microbes Evolved to Tolerate Oxygen - Khademian, Maryam (Trends Microbiol, 2020)
Ancient microbes invented biochemical mechanisms and assembled core metabolic pathways on an anoxic Earth. Molecular oxygen appeared far later, forcing microbes to devise layers of defensive tactics that fend off the destructive actions of both reactive oxygen species (ROS) and oxygen itself. Recent work has pinpointed the enzymes that ROS attack, plus an array of clever protective strategies that abet the well known scavenging systems. Oxygen also directly damages the low-potential metal centers and radical-based mechanisms that optimize anaerobic metabolism; therefore, committed anaerobes have evolved customized tactics that defend these various enzymes from occasional oxygen exposure. Thus a more comprehensive, detailed, and surprising view of oxygen toxicity is coming into view.